Association of Lung CT Findings in Coronavirus Disease 2019 (COVID-19) With Patients' Age, Body Weight, Vital Signs, and Medical Regimen - Al-Shudifat, Abdel-Ellah; Al-Radaideh, Ali; Hammad, Shatha; Hijjawi, Nawal; Abu-Baker, Shaden; Azab, Mohammed; Tayyem, Reema (Frontiers in Medicine, 2022)
Objective: This study aimed to detect the possible association between lung computed tomography (CT) findings in COVID-19 and patients' age, body weight, vital signs, and medical regimen in one of the Middle East countries. Methods: The present cross-sectional study enrolled 230 COVID-19 patients in Prince Hamza Hospital in Jordan. Demographic data, as well as major lung CT scan findings, were obtained from the hospital records of the COVID-19 patients. Results: The main observed major lung changes among the enrolled COVID-19 patients included ground-glass opacification in 47(15.2%) patients and consolidation in 22(7.1%) patients. A higher percentage of patients with major lung changes (24%) was observed among patients above 60 years old, while (50%) of patients with no changes in their lung findings were in the age group of 18-29 years old. Results obtained from the present study showed that only patients with major CT lung changes (9.7%) were prescribed more than three antibiotics. Additionally, 41.6 % of patients with major lung CT scan changes had either dry (31.0%) or productive (10.6%) cough at admission. Conclusion: Several predictors of lung CT scan changes have been detected in this study including age, BMI, medications, the severity of symptoms, and cough at admission.